Haji Abdul Rahman Limbong (1868-1928) fighter against the colonialist - Berhanundin, Abdullah; Kamaruzaman, Yusoff; Mansoureh, Ebrahimi; Ruzaini, Sulaiman@Abd Rahim (2015)
Haji Abdul Rahman Limbong was a religious scholar and a Malay fighter feared by the British colonialists. British had regarded him as a rebel. He was more known to many as a religious teacher, as well as a successful trader and entrepreneur. The present study investigates Haji Abdul Rahman Limbong’s struggle with a focus on three objectives. Firstly, he defended the rights of the settlers and the people of Terengganu from further being governed by the British power. Secondly, he adopted the approach of religious studies to the people, title defence through the Court ruling, opposing to the colonial power through the spirit of Jihad and defending the politics of the state by means of the legislation. Thirdly, he ennobled the Sultanate institution and gave an undivided support to the state administration. A qualitative approach by analyzing available documentation from Public Record Office, Terengganu, is employed to reveal the aims of this study. It is highlighted that defending the people had been the central cause for Haji Abdul Rahman Limbong’s struggle.